2022
DOI: 10.1155/2022/5655767
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Diesel-Degrading Bacteria from Hydrocarbon-Contaminated Sites, Flower Farms, and Soda Lakes

Abstract: Hydrocarbon-derived pollutants are becoming one of the most concerning ecological issues. Thus, there is a need to investigate and develop innovative, low-cost, eco-friendly, and fast techniques to reduce and/or eliminate pollutants using biological agents. The study was conducted to isolate, characterize, and identify potential diesel-degrading bacteria. Samples were collected from flower farms, lakeshores, old aged garages, asphalt, and bitumen soils and spread on selective medium (Bushnell Haas mineral salt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Bacteria are the most diverse and ubiquitous groups of microorganisms known to have imperative functions in the bioremediation of hydrocarbon-contaminated environments. 33 , 34 This work used a BHMS medium enriched with 0.5% kerosene to isolate 7 kerosene-degrading bacteria from hydrocarbon-contaminated settings. Population densities ranging from 10 4 to 10 7 CFU per gram of soil were observed at all sampling sites, which is within the recommended range for efficient hydrocarbon biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria are the most diverse and ubiquitous groups of microorganisms known to have imperative functions in the bioremediation of hydrocarbon-contaminated environments. 33 , 34 This work used a BHMS medium enriched with 0.5% kerosene to isolate 7 kerosene-degrading bacteria from hydrocarbon-contaminated settings. Population densities ranging from 10 4 to 10 7 CFU per gram of soil were observed at all sampling sites, which is within the recommended range for efficient hydrocarbon biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 3) shows the sequential BIS of the soil impacted by 80;000 ppm WMO which decreased to 37;600 ppm in 5 months that shown that it is essential to start biostimulation with detergent for emulsification of hydrocarbons of WMO to ensure its mineralization. Followed by biostimulation with mineral solution to enrich soil with NH 4 NO 3 to balance the C:N ratio necessary for WMO mineralization; in that sense K 2 HPO 4 and KH 2 PO 4 salts accelerated a WMO removal [18]. In the third biostimulation with vermicompost; nitrogenous organic compounds (N) such as urea and nucleotides; as well as organic carbon compounds (C) such as cellobiose and glucose; were added to induce heterotrophic aerobic microorganisms to co-metabolize WMO hydrocarbons and decrease their concentration [19,13,20] While BIS in sequence with V. sativa or green manure enriched the soil with organic N compounds: peptides and amino acids; to maintain the balance of the C:N ratio; as well as with simple organic C compounds to maintain the cometabolism of WMO hydrocarbons to decrease the concentration of WMO [8].…”
Section: Discussionmentioning
confidence: 99%
“…Identification and characterization of microorganisms is one of the most important aspects in the field of microbiology. Phenotypic traits such as morphological, physiological and cultural characteristics are among the classical features used in the identification of microorganisms [9]. However, with the advent of molecular biology techniques, the genotypic methods based on Deoxyribonucleic acid (DNA) offer more precise and best tools for microbial identification in the environment [10].…”
Section: Microorganismsmentioning
confidence: 99%